Higher levels of cardiovascular fitness are associated with better executive function and prefrontal oxygenation in younger and older women - Dupuy, Olivier; Gauthier, Claudine J.; Fraser, Sarah A.; Desjardins-Crèpeau, Laurence; Desjardins, Michèle; Mekary, Said; Lesage, Frederic; Hoge, Rick D.; Pouliot, Philippe; Bherer, Louis (Frontiers in Human Neuroscience, 2015)
Aim: Many studies have suggested that physical exercise training improves cognition and more selectively executive functions. There is a growing interest to clarify the neurophysiological mechanisms that underlie this effect. The aim of the current study was to evaluate the neurophysiological changes in cerebral oxygenation associated with physical fitness level and executive functions. Method: In this study, 22 younger and 36 older women underwent a maximal graded continuous test (i.e., V˙O2max) in order to classify them into a fitness group (higher vs. lower fit). All participants completed neuropsychological paper and pencil testing and a computerized Stroop task (which contained executive and non-executive conditions) in which the change in prefrontal cortex oxygenation was evaluated with near infrared spectroscopy (NIRS). Results: Our findings revealed a Fitness × Condition interaction (p < 0.05) such that higher fit women scored better on measures of executive functions than lower fit women. In comparison to lower fit women, higher fit women had faster reaction times in the Executive condition of the computerized Stroop task. No significant effect was observed in the non-executive condition of the test and no interactions were found with age. In measures of cerebral oxygenation (ΔHbT and ΔHbO2), we found a main effect of fitness on cerebral oxygenation during the Stroop task such that only high fit women demonstrated a significant increase in the right inferior frontal gyrus. Discussion/Conclusion: Higher fit individuals who demonstrate better cardiorespiratory functions (as measured by V˙O2max) show faster reaction times and greater cerebral oxygenation in the right inferior frontal gyrus than women with lower fitness levels. The lack of interaction with age, suggests that good cardiorespiratory functions can have a positive impact on cognition, regardless of age.